Diabetes and Lung Cancer: A Sweet and Sour Relationship - Paraskevas, Andreas; Bellou, Elena; Keramida, Elli; Bracka, Irma; Gkriniouk, Christina; Mazarakis, Spyros; Karampinis, Ioannis; Demertzis, Panagiotis; Hardavella, Georgia (Current Respiratory Medicine Reviews, 2022)
Introduction: Diabetes mellitus and lung cancer are two highly prevalent diseases on a global scale. The association between these two diseases has been the subject of study of many cohorts in the past, some of which presenting inconclusive results. Aim: To present existing evidence regarding the association of diabetes with lung cancer risk and survival as well as the impact of metformin and insulin on lung cancer. Methods: A narrative review of all the relevant published literature known to the authors was conducted. The references were identified by searching the Pubmed online database using the keywords such as diabetes and lung cancer risk, diabetes and lung cancer survival rates, metformin and lung cancer, insulin and lung cancer. Results: Although previous epidemiologic studies have failed to report any significant causal effect of diabetes on lung cancer risk, recent evidence from 2 large scale meta-analyses of observational studies and other studies showed a statistically significant correlation between nonsmoker diabetics and lung cancer risk (RR, 1.11; 95% CI, 1.02-1.20; I2 = 46.1% and RR, 1.14; 95% CI, 1.09-1.20; I2 = 0%). Recent evidence has shown that metformin is related to a lower risk of lung cancer incidence among never-smokers diabetic patients (HR, 0.57;95% CI, 0.33-0.99) and improved overall survival rates (HR=0.77, 95%CI=0.66-0.9, P=0.001) regardless of the histological type of lung cancer. On the other hand, a recently published large population-based retrospective cohort study has concluded that human insulin is associated with an increased risk of lung cancer (HR 1.545, 95% CI: 1.478-1.614). Interestingly, metformin has been reported to have an anti-resistant effect on lung cancer patients who are on Epidermal Growth Factor Receptor- Tyrosine Kinase Inhibitors, offering some protection against resistance to therapy. Conclusion: Published evidence shows that diabetes mellitus is associated with an increased risk of lung cancer and worse survival rates. Metformin plays a protective role in lung cancer pathogenesis and is also associated with prolonged progression-free survival in lung cancer patients with diabetes. There is a significant association between human insulin use and lung cancer risk. More randomized controlled studies are required to establish the positive association of diabetes and anti-diabetic drugs with lung cancer, taking into further consideration gender and lung cancer pathology as well as possible confounders such as smoking habits that can influence the results of these studies.
Keywords: risk